2020
DOI: 10.5603/fhc.a2020.0003
|View full text |Cite
|
Sign up to set email alerts
|

Search of reference biomarkers reflecting orbital tissue remodeling in the course of Graves’ orbitopathy

Abstract: Introduction. Graves' orbitopathy (GO) is a complication in Graves' disease (GD) that causes disfigurement and sometimes blindness. The pathogenesis of GO remains unknown, while its symptoms demonstrate dependence between the thyroid gland and the orbit. The ongoing inflammatory process in retrobulbar tissue results in its remodeling characterized by increased volume of the orbital contents involving adipose tissue, with fibrosis and adipogenesis as predominant features. This study was aimed at the immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…IGF-1R is another autoantigen involved in the pathogenesis of TED [ 11 , 69 ]. Recent studies have reported that expression of the IGF-1R protein is higher in orbital tissue from TED patients than in that from controls [ 70 , 71 ]. However, despite the fact that many previous studies confirmed the involvement of IGF-1R in TED, activation of IGF-1R on OFs after binding by stimulating antibodies (IGF-1R-Ab) remains controversial [ 56 ].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-1R is another autoantigen involved in the pathogenesis of TED [ 11 , 69 ]. Recent studies have reported that expression of the IGF-1R protein is higher in orbital tissue from TED patients than in that from controls [ 70 , 71 ]. However, despite the fact that many previous studies confirmed the involvement of IGF-1R in TED, activation of IGF-1R on OFs after binding by stimulating antibodies (IGF-1R-Ab) remains controversial [ 56 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…High serum levels of BAFF were reported in patients with TED [ 72 ]. Expression of the BAFF protein in the orbital tissue of TED patients is higher than that in healthy controls [ 71 ].…”
Section: Pathogenesismentioning
confidence: 99%
“… 20 Several studies have implicated the inflammatory process in the manifestation of TAO. 21 , 22 In fact, the NLRP3 inflammasome is known to activate interleukin (IL) 1B, 23 which in turn stimulates an increase of hyaluronan accumulation in OFs 24 and also increases levels of IL-6 and prostaglandin E2. 20 , 25 …”
Section: Introductionmentioning
confidence: 99%